2009
DOI: 10.2174/18744281003010011
|View full text |Cite
|
Sign up to set email alerts
|

Lipoma in the Soft Tissues of the Floor of the Mouth: A Case Report

Abstract: Lipomas are common benign soft tissue neoplasms of mature adipose tissue. Most of lipomas develop in the subcutaneous tissues but deeper tissues may be involved as well; the oral cavity is not commonly affected. The overall incidence in the oral cavity is thought to be between 1% and 4.4% of all benign oral lesions. Oral lipomas can occur in various anatomic sites including the major salivary glands, buccal mucosa, lip, tongue, palate, vestibule, and floor of mouth. Although benign in nature, their progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
1
6
0
2
Order By: Relevance
“…They may be single or multiple, encapsulated or unencapsulated. 8,15,16 In this study, all lesions were found to be compatible with the general clinical features.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…They may be single or multiple, encapsulated or unencapsulated. 8,15,16 In this study, all lesions were found to be compatible with the general clinical features.…”
Section: Discussionsupporting
confidence: 71%
“…Although they are asymptomatic, they can interfere with functions such as speech and chewing in advanced cases. 15,16 Lesions may also cause a feeling of discomfort. They may be single or multiple, encapsulated or unencapsulated.…”
Section: Discussionmentioning
confidence: 99%
“…Oral lipomas are found commonly in males above 40 years of age. 20 However, our case was a female patient aged 65 years. The buccal mucosa and the buccal vestibule are common sites where oral lipomas occur.…”
Section: Discussionmentioning
confidence: 78%
“…They are relatively rare in the mouth and the maxilla-facial region 3,4 . The case above fits into these criteria and other reports in the literature; it is atypical in its size (5.0 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Lipomas of the mouth are benign tumors; they grow slowly, do not infiltrate other tissues, do not ulcerate, and are painless. They are relatively rare in the mouth and the maxilla-facial region 3 , 4 . The case above fits into these criteria and other reports in the literature; it is atypical in its size (5.0 cm).…”
Section: Discussionmentioning
confidence: 99%